2019–2020 Florida Citrus Production Guide: Pesticide Resistance and Resistance Management - Lauren M. Diepenbrock; Megan M. Dewdney; Ramdas Kanissery (EDIS, 2019)
This 4-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Lauren M. Diepenbrock, Megan M. Dewdney, and Ramdas Kanissery, and published by the Entomology and Nematology Department, March 2019.